Reproductive outcomes in adolescents who had a previous birth or an induced abortion compared to adolescents' first pregnancies - Wenzlaff Paul; Schücking Beate A; Reime Birgit (BMC, 2008)
Abstract Background Recently, attention has been focused on subsequent pregnancies among teenage mothers. Previous studies that compared the reproductive outcomes of teenage nulliparae and multiparae often did not consider the adolescents' reproductive histories. Thus, the authors compared the risks for adverse reproductive outcomes of adolescent nulliparae to teenagers who either have had an induced abortion or a previous birth. Methods In this retrospective cohort study we used perinatal data prospectively collected by obstetricians and midwives from 1990-1999 (participation rate 87-98% of all hospitals) in Lower Saxony, Germany. From the 9742 eligible births among adolescents, women with multiple births, >1 previous pregnancies, or a previous spontaneous miscarriage were deleted and 8857 women <19 years remained. Of these 8857 women, 7845 were nulliparous, 801 had one previous birth, and 211 had one previous induced abortion. The outcomes were stillbirths, neonatal mortality, perinatal mortality, preterm births, and very low birthweight. Bivariate and multivariable logistic regression models were conducted. Results In bivariate logistic regression analyses, compared to nulliparous teenagers, adolescents with a previous birth had higher risks for perinatal [OR = 2.08, CI = 1.11,3.89] and neonatal [OR = 4.31, CI = 1.77,10.52] mortality and adolescents with a previous abortion had higher risks for stillbirths [OR = 3.31, CI = 1.01,10.88] and preterm births [OR = 2.21, CI = 1.07,4.58]. After adjusting for maternal nationality, partner status, smoking, prenatal care and pre-pregnancy BMI, adolescents with a previous birth were at higher risk for perinatal [OR = 2.35, CI = 1.14,4.86] and neonatal mortality [OR = 4.70, CI = 1.60,13.81] and adolescents with a previous abortion had a higher risk for very low birthweight infants [OR = 2.74, CI = 1.06,7.09] than nulliparous teenagers. Conclusion The results suggest that teenagers who give birth twice as adolescents have worse outcomes in their second pregnancy compared to those teenagers who are giving birth for the first time. The prevention of the second pregnancy during adolescence is an important public health objective and should be addressed by health care providers who attend the first birth or the abortion and the follow-up care. Also, health care workers should attempt to improve the pregnancy outcomes of subsequent teenage pregnancies by addressing modifiable risk factors, for example, supporting smoking cessation and utilization of prenatal care.